An Enhanced Video Assisted Health Education System - et. al., k. Paavizhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Methodology plays a dominant role in any type of research. Research is a well-planned, systematic and cautious endeavour. It is a process, a way, a method, a means of finding out something new, or getting better understanding of something that we know already. A better understanding will take us nearer to reality and lead to better, wider and more forms of applicability of the phenomenon being researched. Selection of the research method was fully depending upon the nature of the study units to be followed.The purpose of the study was designed to found out the effectiveness of An Enhanced Video Assisted Health Education Module (VAHEM) in enhancing knowledge, Skill and Attitude among Secondary Teacher Trainees.